A “Concrete Desert” That Has Become a Green Meadow? Questions About Late-Socialist Block Housing in the Context of the Phenomenon of Their Socio-Economic Vitality Based on the Case of Poland - Nowak, Marek; Błażejczyk-Majka , Lucyna; Palicki, Sławomir (Porównania, 2024)
The issue of late-socialist block housing estates has been marked for years by ambivalence, the sources of which are strongly connected mainly with the ideological foundations of the systemic transformation. The aforementioned ambivalence is inscribed in the perception of block housing in the context of terms such as: “concrete desert”, “bedroom”, or ghettoized space (a reference to the subculture of the 1990s, the so-called blokersi), etc. Contemporary research indicates that large housing estates resist the processes of social degradation. This triggers discussions on the use of metaphors of “concrete desert” and “meadow” in the context of late-socialist block housing estates. This article is an attempt to interpret the available research data to answer questions about the condition of block housing in the third decade of the twenty-first century. The answers are framed in three perspectives: socio-spatial, neighboring and economic. The empirical basis for the interpretation is primarily the quantitative research carried out in 2018 by the then Institute of Sociology of the Adam Mickiewicz University, which aimed to describe the specifics of neighborhoods in block housing.